1995
DOI: 10.1029/94jc02214
|View full text |Cite
|
Sign up to set email alerts
|

Copepod grazing and fine‐scale distribution patterns during the Marine Light‐Mixed Layers experiment

Abstract: The mesozooplankton in the upper 100 m at 59øN, 21øW were dominated by the copepodite stages of Calanus finmarchicus in both May and August 1991. Abundance of C. finmarchicus in the upper 20 m of the water column was 800 m -3 in May and 200 m -3 in August. Although hydrographic conditions changed from well mixed to stratified between May and August, the fine-scale vertical distribution pattern of C. finmarchicus was essentially the same during these two surveys of the Marine Light-Mixed Layers site. Copepodite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 33 publications
(1 reference statement)
1
17
0
Order By: Relevance
“…Evidence for this comes from both field observations (e.g. Cowles & Fessenden 1995, Montagnes et al 1999, Dekshenieks et al 2001, Alldredge et al 2002, Rines et al 2002 and experimental studies (Speekmann et al 2000, Lougee et al 2002, Bochdansky & Bollens 2004, Clay et al 2004, Ignoffo et al 2005. It is possible that more highly vertically resolved sampling of micro-and nanoplankton in the SFE could reveal greater heterogeneity in vertical distributions than the results presented here based on 2 m depth increments.…”
mentioning
confidence: 41%
“…Evidence for this comes from both field observations (e.g. Cowles & Fessenden 1995, Montagnes et al 1999, Dekshenieks et al 2001, Alldredge et al 2002, Rines et al 2002 and experimental studies (Speekmann et al 2000, Lougee et al 2002, Bochdansky & Bollens 2004, Clay et al 2004, Ignoffo et al 2005. It is possible that more highly vertically resolved sampling of micro-and nanoplankton in the SFE could reveal greater heterogeneity in vertical distributions than the results presented here based on 2 m depth increments.…”
mentioning
confidence: 41%
“…The cell size of the majority of dinoflagellates in the incubation water was much less than the cell size of the dominant diatoms throughout the investigation (see Results). Experiments conducted by Cowles et al (1988) have demonstrated that food selection by copepods can occur on the basis of food quality. Previous studies have shown that egg production is related Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…2 ) goodnessof-fit test (Cowles 1979), as described in detail by Sokal and Rohlf (1969). The frequency distribution of food types in the diet was compared with that in the environment.…”
Section: Calculation Of Grazing Impact-thementioning
confidence: 99%
See 1 more Smart Citation
“…, and had the opportunity also to estimate zooplankton grazing from microand mesozooplankton. Mesozooplankton removed between 1-5% of phytoplankton standing stock per day (Cowles et al, 1995). Mesozooplankton are of course unlikely to be included in the sample size typical of primary production incubations.…”
mentioning
confidence: 99%